Pembelajaran Menggambar Dengan Teknik Digital Pada Beginner Class di Ageru Art Studio - Banifa Anggraeni, Enggar (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
In the modern era, drawing is no longer limited to traditional methods like paper and pencil—it can also be done digitally. One institution offering digital drawing training as a form of non-formal education is Ageru Art Studio, which provides a Beginner Class for novice artists. This research aims to explore the learning concept at Ageru Art Studio, particularly in its Beginner Class, as a digital drawing training center. Using a qualitative method with a participatory approach, the researcher observed and actively engaged in the learning process. The findings reveal that the operational learning concept is managed directly by operational managers, with close collaboration between tutors and students. The Beginner Class is divided into two levels: Basic Class, which focuses on teaching elementary school students how to draw and color using a tablet, and Basic Manga Kids, which introduces students to manga-style drawing techniques. However, challenges such as insufficient tutors and low student attendance occasionally disrupt the class’s conduciveness.